A critical analysis of the legality of retroactive fiscal legislation and the remedies available to taxpayers - De Villiers, Christoff De Wet (Department of Finance and Tax, 2022)
‘Uncertain law also penalizes those anxious to obey it and eventually creates contempt for the law. Uncertain law will thus erode the confidence of taxpayers in the system and their willingness to support and comply with the system.' Retroactive fiscal legislation leaves taxpayers with little to no tax certainty, with only about two months of transactional certainty each tax year not subject to any potential retroactive draft fiscal legislation - from when the amendment act from the prior legislative amendment cycle is promulgated until the Budget Speech which sets in motion the new legislative amendment cycle. Arguably, economic activity and tax morality could increase should more certainty exist as to what types of retroactive fiscal legislation are permissible, in which circumstances it is permitted and the remedies available to taxpayers in cases where such legislation adversely affects their vested rights. This research aims to consider the legality of retroactive fiscal legislation to provide much-needed tax certainty. This will be done by analysing the rules under the common law, statute law (being the Interpretation Act) and the Constitution. The conclusion reached under the common law is that regarding fully completed transactions, the presumption against retroactivity will provide an effective remedy to taxpayers should the retroactive legislation not explicitly provide that it will apply to completed transactions. Under statute law, the treatment of statues which are subject to commencement provision are dealt with similarly under the Interpretation Act and the proposed Interpretation of Legislation Bill, in that neither contains an outright prohibition on retroactive legislation. Under the Constitution, a challenge based on either the rule of law or the doctrine of separation of powers will most likely not be successful. A challenge in terms of section 25 of the Constitution would be the constitutional remedy most likely to succeed. A challenge under section 25 of the Constitution requires a two-stage test: Firstly, it needs to be determined if the deprivation of property was arbitrary for purposes of section 25 of the Constitution. Secondly, it needs to be determined if section 25 of the Constitution's limitation is justifiable under section 36 of the Constitution. The deprivation of property will be arbitrary if sufficient reasons are not provided. If found to be arbitrary, then the judiciary must declare such legislation unconstitutional without the need to consider section 36 of the Constitution. Should an assessment under section 36 of the Constitution be required, the competing values need to be measured against each other and an assessment made based on proportionality. Section 36(1)(e) of the Constitution suggests that prospective legislation is preferred to retroactive legislation, and that means less restrictive than retroactive fiscal legislation should be relied on if they exist. Based on the analysis in this paper, it is respectfully submitted that the taxpayers in Pienaar Brothers should have had an effective remedy in terms of section 25 of the Constitution, read with section 36(1)(e) of the Constitution, as less restrictive means were available to the Commissioner in the form of the general anti-avoidance rules. The retroactive amendments were also not of general application and the taxpayers did not receive adequate warning. Irrespective of a successful constitutional challenge, the taxpayers in Pienaar Brothers also had a remedy available to them under the common law presumption against retroactivity (as applied to the completed transaction). The retroactive amendments negatively impacted their vested rights without specifically stating that it would apply to completed transactions. It is unfortunate that the matter was not taken on appeal, as judicial precedent is much needed on the topic of retroactive fiscal legislation and completed transactions.